Between GPA and Peace of Mind Academic Pressure vs Mental Health of Gen Z - Erni Susanty Tahir; Fatika Puteri Rosyi Prabowo (International Journal of Social Science and Humanity, 2025)
Generation Z students face increasingly complex academic challenges within the competitive higher education ecosystem. The pressure to maintain academic performance, social expectations, and intense digital exposure contribute to rising mental health issues such as stress, anxiety, and burnout. This study aims to analyze the relationship between academic pressure and the psychological condition of Gen Z students using a quantitative-descriptive approach through an online survey. The research instrument adapted the Academic Stress Scale (ASS) and the Depression Anxiety Stress Scale (DASS-21). The results show that the majority of respondents experience significant academic pressure, which correlates positively with symptoms of stress and anxiety. These findings highlight the importance of educational system reform that not only emphasizes academic performance but also supports students' mental well-being. Higher education institutions are expected to provide safe spaces, reliable counseling services, and more empathetic teaching approaches in response to the mental health issues facing this generation.